2021
DOI: 10.1155/2021/9931535
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Adult Patients Receiving Cervical Fusion for Fresh Subaxial Cervical Injury: The Role of Associated Spinal Cord Injury

Abstract: Purpose. To study postoperative Health-Related Quality of Life (HRQOL) after instrumented fusion for fresh subaxial cervical trauma and the effect of spinal cord injury (SCI). Methods. From a total of 65 patients, 17 (26%) patients suffered on admission from SCI. Twenty-five patients underwent anterior, 25 posterior, and 15 circumferential cervical surgery for a single cervical injury. Sagittal roentgenographic parameters were measured in 65 age-matched asymptomatic controls and in patients on admission, eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
2
1
0
3
Order By: Relevance
“…We also found a negative correlation of C0-C2 relative to CL in both groups postoperatively. Similar result has been reported by other authors as follows: A study was done by Korovessis et al 23 to investigate HLQOL after instrumentation fusion after subaxial cervical trauma, and the authors found that C0-C2 had a negative correlation with CL in patients who underwent fusion surgery relative to the control health individual. A study by Nojiri et al 24 in asymptomatic health individual established the standard values of upper and lower cervical regions, and the authors found notable negative correlations between C0-C2 and CL.…”
Section: Discussionsupporting
confidence: 88%
“…We also found a negative correlation of C0-C2 relative to CL in both groups postoperatively. Similar result has been reported by other authors as follows: A study was done by Korovessis et al 23 to investigate HLQOL after instrumentation fusion after subaxial cervical trauma, and the authors found that C0-C2 had a negative correlation with CL in patients who underwent fusion surgery relative to the control health individual. A study by Nojiri et al 24 in asymptomatic health individual established the standard values of upper and lower cervical regions, and the authors found notable negative correlations between C0-C2 and CL.…”
Section: Discussionsupporting
confidence: 88%
“…a1 was negative if the cervical spine was anteriorly convex in hyper exion and a2 was negative if the cervical spine was deformed and retro exed in hyperextension. ROM = a1 + a2 [11]. We measured and recorded the patient's cervical mobility preoperatively, and at 1 and 3 months of discharge, through the patient's cervical hyperextension hyper exion slices at each follow-up visit.The quality of life was measured by the SF-36 (quality of life assessment scale) scores,The SF-36 scale includes 8 dimensions, with a total of 36 items.…”
Section: Discussionmentioning
confidence: 99%
“…Die Behandlungsergebnisse nach HWS-Verletzungen hängen im Wesentlichen vom Grad der neurologischen Verletzung ab [69]: Verständlicherweise hat eine Rückenmarkverletzung einen starken negativen Einfluss auf die Lebensqualität [69].…”
Section: Behandlungsergebnisse Und Prognoseunclassified
“…Ohne Rückenmarkverletzung berichten 81% der Patienten über ein exzellentes oder gutes Ergebnis nach >5 Jahren [69,70]. Die Rückkehr in den alten Beruf gelingt ebenfalls etwa 84% [70].…”
Section: Behandlungsergebnisse Und Prognoseunclassified
See 1 more Smart Citation